2008
DOI: 10.1001/archinte.168.7.728
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cancer Risk Perception and Screening Behavior Among Diverse Women

Abstract: Background: We measured the perception of breast, cervical, and colon cancer risks and screening in diverse women to examine the association between risk perception and screening behavior. Methods: Cross-sectional telephone and in-person interviews of women aged 50 to 80 years were conducted in English, Spanish, or Chinese. The women were recruited from primary care practices in San Francisco, California (academic general internal medicine, family medicine, women's health practices, a community-based clinic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 26 publications
(13 reference statements)
4
87
1
Order By: Relevance
“…19 Perhaps black women perceive a higher CRC risk because they more often see the diagnosis made in family members. Kim et al 20 found that family history was a predictor of perceived risk for CRC among a group of diverse women. The opposite trend, although not statistically significant, is seen in black men, in which obese black men see themselves as at decreased risk for cancer compared with nonobese black men.…”
Section: Discussionmentioning
confidence: 99%
“…19 Perhaps black women perceive a higher CRC risk because they more often see the diagnosis made in family members. Kim et al 20 found that family history was a predictor of perceived risk for CRC among a group of diverse women. The opposite trend, although not statistically significant, is seen in black men, in which obese black men see themselves as at decreased risk for cancer compared with nonobese black men.…”
Section: Discussionmentioning
confidence: 99%
“…However, Asians stated that they would be less likely than Whites to obtain colonoscopy after hearing the risks and benefits. While we do not know the reasons for these differences, these race/ethnic differences may be partly due to the difference in risk perception between these groups, 5 and being Latino or Asian was also an independent predictor of willingness and intention to undergo CRC screening.…”
Section: Discussionmentioning
confidence: 81%
“…Risk perception is different than actual risk; thus, a person who perceives herself to be at increased risk may or may not actually be at increased risk. We had previously shown that perceived risk was significantly associated with higher use of CRC screening tests, 5 but these women uniformly overestimated their numerical risk of CRC compared to population rates. Because of the importance of risk perception as a motivator of behavior, future research should address whether targeting perceived risk may result in changes in CRC screening behavior and clarify the use of different measures to assess perceived risk in diverse populations.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations